Optimized Hybrid Renewable Energy System for Sustainable Electric Vehicle Charging: Integration of Photovoltaic and Wind Power With Advanced Control Strategies - R. Tharwin Kumar; C. Christober Asir Rajan (IEEE Access)
In an era where environmental and economic priorities increasingly intersect, advancing technologies are transforming Electric Vehicles (EVs) into more sustainable options. This research presents a novel Hybrid Energy System (HES) that integrates Photovoltaic (PV) and wind power systems into the grid, providing a continuous, reliable power supply specifically for EV charging. The core innovation lies in the design and implementation of a High Gain Bidirectional Modified Zeta (HGBMZ) converter, which significantly enhances PV system efficiency by boosting voltage levels. To optimize power extraction, the system employs an advanced Social Spider Optimization Algorithm (SSOA)-assisted Fuzzy controller for precise Maximum Power Point Tracking (MPPT), ensuring superior converter performance and maximal energy harvesting. A Doubly Fed Induction Generator (DFIG) driven by a Proportional Integral (PI) controller stabilizes the wind component, maintaining voltage levels and system stability across variable conditions. A key feature of this HES is its ability to feed surplus energy back into the grid, facilitated by a PI controller for effective control of voltage and synchronization during peak demand cycles. Validated through MATLAB simulations, the proposed system achieves an impressive converter efficiency of 93.04% and a low Total Harmonic Distortion (THD) of 3.21%. Laboratory validation further confirms a THD of 4.32%, establishing the system as a sustainable and optimized solution for EV charging.